Hydroclimatic extremes and food security hotspots in West Africa: evidence from rainfall–yield interactions - Obahoundje, Salomon; Tilahun, Seifu A.; Schmitter, Petra (Frontiers in Climate, 2025)
IntroductionRainfall regimes across West Africa have undergone substantial transformations over the past four decades, with profound implications for rainfed agriculture and food security. However, limited understanding persists on how rainfall extremes translate into spatially differentiated crop yield responses across agroclimatic zones.MethodsThis study integrates multi-decadal climate datasets with crop yield data from the Global Dataset of Historical Yields (GDHY) to assess the sensitivity of maize, rice, and soybean yields to hydroclimatic extremes across six agroclimatic zones. A sensitivity analysis using an Ordinary Least Squares regression framework quantified crop yield responses to key climatic variations across multi-decadal timescales, agroclimatic zones, and administrative units.ResultsResults reveal marked north–south contrasts in rainfall extremes. In the Sahelian and Sudanian zones, seasonal rainfall increased by 5%–25% since the 1990s and up to 80% in the Northern Sahel by 2024, largely driven by more frequent wet days and intensified rainfall events. These trends heighten flood and erosion risks in northern regions. Conversely, the Guinean zones exhibit stagnating or declining rainfall, coupled with over a 90% increase in consecutive dry days in Central Guinea, signaling intensifying drought stress. Crop yield responses associated with these hydroclimatic patterns. Maize yields increased by 40%–50% in the Sahelian, Sudanian, and parts of the Guinean zones, while rice yields declined by 20%–50% in Nigeria’s Sudanian and Eastern Guinea regions. Soybean showed localized yield gains but remained extremely sensitive to rainfall deficits and heat extremes.DiscussionBy linking rainfall variability to spatially explicit yield responses, this study provides a novel multi-decadal sensitivity framework for evaluating climate impacts on agriculture in West Africa. The findings highlight the urgent need for region-specific, climate-smart adaptation strategies, emphasizing flood and erosion management in the north and drought resilience in the south, to sustain food production under increasing climatic variability.